Physical activity, adiposity and hypertension among patients of public healthcare system - Bruna Camilo Turi; Jamile Sanches Codogno; Rômulo Araújo Fernandes; Henrique Luiz Monteiro (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2014)
INTRODUCTION: Hypertension is a chronic disease that requires special attention in identifying comorbidities or risk factors including inactivity and obesity. Considering that a large proportion of the Brazilian population is hypertensive, obese, and sedentary, the relationship among these variables in the context of the public health system is unclear. OBJECTIVE: To assess the association among physical activity, markers of adiposity, and hypertension in adult users of the public healthcare system in the city of Bauru, São Paulo, Brazil. METHODS: The study was conducted in five Basic Health Units in Bauru, São Paulo, and consisted of 963 patients. Data were collected from habitual physical activity and previous (childhood and adolescence), education, purchasing power and anthropometric markers of overall and abdominal obesity. RESULTS: The incidence of hypertension was 76.8%. Significant associations were found among sedentarism, presence of total and abdominal obesity, with the higher incidence of hypertension. It was also observed that the magnitude of association between hypertension and adiposity increased with decreased involvement in physical activity. CONCLUSION: Further investigations are needed to analyze the occurrence of overweight and obesity in people suffering from chronic diseases in order to prevent future complications.